2009
DOI: 10.1346/ccmn.2009.05706012
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate-Induced Structural Perturbation of Al Hydroxides

Abstract: The chemistry of Al transformation has been well documented, though little is known about the mechanisms of structural perturbation of Al precipitates by carbonates at a molecular level. The purpose of the present study was to investigate the structural perturbation of Al precipitates formed under the influence of carbonates. Initial carbonate/Al molar ratios (MRs) used were 0, 0.1, and 0.5 after aging for 32 days, then the samples were analyzed by X-ray absorption near edge structure spectroscopy (XANES), X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…In the absence of LMW organic acids gibbsite was formed, which is in agreement with other reported studies (Kwong and Huang, 1979b). Some other researchers (Hu et al, 2008;Zhang et al, 2009) have observed bayerite and/or pseudoboehmite in addition to gibbsite, which was attributed to differences in the preparation method, including such factors as the initial Al concentration, titration rate, pH, and rate of precipitation (Huang and Violante, 1986;Violante and Huang, 1993).…”
Section: Xrd Analysissupporting
confidence: 90%
See 4 more Smart Citations
“…In the absence of LMW organic acids gibbsite was formed, which is in agreement with other reported studies (Kwong and Huang, 1979b). Some other researchers (Hu et al, 2008;Zhang et al, 2009) have observed bayerite and/or pseudoboehmite in addition to gibbsite, which was attributed to differences in the preparation method, including such factors as the initial Al concentration, titration rate, pH, and rate of precipitation (Huang and Violante, 1986;Violante and Huang, 1993).…”
Section: Xrd Analysissupporting
confidence: 90%
“…3), the absorption peak characteristics of crystalline Al (oxy)hydroxides virtually disappeared. From 3700 to 3300 cm À1 , a single broad peak was observed, which was attributed to the formation of noncrystalline Al precipitates (Zhang et al, 2009). The absorption peaks at 1409 and 1663 cm À1 for the citrate/Al MR = 0.1 system and the 1407 and 1653 cm À1 for malate/Al MR = 0.1 system were assigned to the c(COO À ) stretching vibration of free carboxylate groups and the c(COO À ) stretching vibration of coordinated carboxylate groups with Al (Liu et al, 2006;Pasilis and Pemberton, 2008 system, the peaks at 1612 and 1582 cm À1 were assigned to a c(C-C) ring vibration, the peak at 1477 cm À1 was the C-C ring bonds of the salicylate complexing with Al, the peak at 1384 cm À1 was assigned to c(COO À ) stretching vibration and the peak at 1267 cm À1 was assigned to C-O stretching of the phenolic OH group (Biber and Stumm, 1994).…”
Section: Ftir Analysismentioning
confidence: 99%
See 3 more Smart Citations